TRANSVERSE BODY DIMENSIONS IN UKRAINIAN MEN AND WOMEN WITH VARIOUS FORMS OF URTICARIA - Aladwan, A.M.A.; Dmytrenko, S.V.; Smolko, D.G.; Melnyk, T.V.; Gunas, I.V. (World of Medicine and Biology, 2024)
In young Ukrainian men and women with acute and chronic urticaria of a mild and severe course, reliable or trends of differences in the transverse dimensions of the chest, shoulder width and pelvic dimensions from practically healthy Ukrainian men and women of the same age were established. Between the corresponding groups of sick men or sick women, only a few reliable or trends of differences in the transverse dimensions of the body were established. Pronounced manifestations of sexual dimorphism of the transverse dimensions of the body were established – in all groups of male patients, shoulder widths were significantly larger, as well as in men with severe acute and chronic urticaria, larger values of all chest diameters; and in patients with acute urticaria of a mild course in women – significantly larger values of all pelvic distances.